The Effect of the Realistic Mathematics Education (RME) Learning Model on the Second-Grade Elementary Students’ Mathematics Learning Outcomes - Simamora, Sarimauli; Juliana; Maya Sari Sembiring, Heka; Wulan Sari HS, Dyan; Sofia Tanjung, Darinda; Samuel Prayuda, Meikardo (Jurnal PAJAR (Pendidikan dan Pengajaran), 2024)
The present study discusses the effect of the realistic mathematics education learning model on the mathematics learning outcomes of grade II students of State Elementary School 173472 Sijarango, Pakkat District, Humbang Hasundutan in the academic year 2023/2024. The independent variable is the realistic mathematics education learning model (X) and the dependent variable is the students' mathematics learning outcomes (Y). The research method used is an experimental method with a quantitative research type and the number of research samples was 27 students based on the purposive sample technique. The data for the realistic mathematics education learning model was obtained from a questionnaire distributed to students and the students' mathematics learning outcomes were obtained from the students' Pretest and Posttest scores in the academic year 2023/2024. The students' mathematics learning outcomes show that the average score of class II Pretest students is 58.51 while the average Posttest score is 88.33. Furthermore, the results of the hypothesis testing show that the t_count is 4.570 while the t_table is 2.052. It is proven that Ho is rejected and Ha is accepted. Through the t-test, it can be concluded that there is a significant positive influence between the realistic mathematics education learning model on the mathematics learning outcomes of class II students.